Peranan Faktor Demografik Dalam Hubungan Antara Motivasi, Gaya Pembelajaran, Disiplin Pembelajaran dan Pencapaian Akademik Pelajar: The Role of Demographic Factors in the Relationship Between Motivation, Learning Style, Learning Discipline and Student Academic Achievement - Chik, Zamri; Abdullah, Abdul Hakim; Muda, Habsah; Istikomah, Istikomah (Halaqa: Islamic Education Journal, 2018)
Demographic factors are factors that determine the relationship between motivation, learning style and learning discipline on the academic achievement of Islamic education. Indeed, this study was carried out to determine the relationship between the motivation, learning style and learning discipline to the academic achievement of Islamic education. A total of 260 fourth graders become study samples. The study shows that male genitalia have a modest impression (moderator) that is significant in the relationship between motivation and academic achievement, but female females are not and the conclusion that females have a full moderation in this relationship. Both jantina (male and female) do not have a significant moderating impression in the relationship between motivation and learning discipline and the conclusion that jantina does not have a simple moderation effect in this relationship. Furthermore, the two jantinas (male and female) have a significant moderating impression in the relationship between learning styles and academic achievement and the conclusion is that Jantina has a partial mediation in this relationship. Whenever, female marriage is a significant moderator in the relationship between the discipline of learning and academic achievement, but male sex is not and the conclusion that the female has a full moderation in this relationship.